The Azores, Madeira, Canaries, and Cape Verde islands, and Africa from cape Spartel to cape Palmas. - United States. Hydrographic Office. (Washington, Govt. print. off., 1908)
Cover-title:: North Atlantic islands and Africa from cape Spartel to cape Palmas. Mode of access: Internet.